TAFSIR ATAS ISLAM NUSANTARA (Dari Islamisasi Nusantara Hingga Metodologi Islam Nusantara) - Abdul Moqsith (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
This article tries to explain the basic understanding of the term ‘Islam Nusantara’ (Archipelagic Islam), including its history and methodology. Academically, this article bases its premis on the main references written by Islamic scholars who have been proposing the importance of linking Islam Nusantara with the culture of the people in the archipelago. By referring to those references, it is noticeable how the dialectics of Islam and culture has evolved in the making of a unique Islam Nusantara. Since its inception, Islam Nusantara has become a heated discussion in the public discourse. Controversies and misunderstandings have occurred with those who support and against it. In the circle of NU (Nahdhatul Ulama), there is a group who prefer the term Islam rahmatan lil ‘alamiin than Islam Nusantara. This article aims to minimize the negative accusation against the concept of Islam Nusantara like the following phrases; Islam Nusantara has the potency to gnawthe principle teachings of Islam, or Islam Nusantara has deviated from the teaching of Ahlus Sunnah Waljama’ah (Aswaja).